A Marine Collagen-Based Biomimetic Hydrogel Recapitulates Cancer Stem Cell Niche and Enhances Progression and Chemoresistance in Human Ovarian Cancer - Moon, SooHyeon (Mar Drugs, 2020)
Recent attention has focused on the development of an effective three-dimensional (3D) cell culture system enabling the rapid enrichment of cancer stem cells (CSCs) that are resistant to therapies and serving as a useful in vitro tumor model that accurately reflects in vivo behaviors of cancer cells. Presently, an effective 3D in vitro model of ovarian cancer (OC) was developed using a marine collagen-based hydrogel. Advantages of the model include simplicity, efficiency, bioactivity, and low cost. Remarkably, OC cells grown in this hydrogel exhibited biochemical and physiological features, including (1) enhanced cell proliferation, migration and invasion, colony formation, and chemoresistance; (2) suppressed apoptosis with altered expression levels of apoptosis-regulating molecules; (3) upregulated expression of crucial multidrug resistance-related genes; (4) accentuated expression of key molecules associated with malignant progression, such as epithelial–mesenchymal transition transcription factors, Notch, and pluripotency biomarkers; and (5) robust enrichment of ovarian CSCs. The findings indicate the potential of our 3D in vitro OC model as an in vitro research platform to study OC and ovarian CSC biology and to screen novel therapies targeting OC and ovarian CSCs.